Information Processing Variables in Learning to Solve Problems. - Mayer, Richard E. (Review of Educational Research)
This article presents three general models of the internal processing involved in learning to solve problems and its relation to both external instructional procedures and learning outcome variables. In this article, empirical data from a series of experiments on teaching probability concepts to college students are compared with the predictions of each model. The study of the learning process provides some suggestions concerning the conditions of learning. The study also suggested the implications of the three conditions for providing meaningful learning and for diagnosing failures in instruction.